Ventilatory Efficiency in Children and Adolescents Born Extremely Preterm - Hestnes, Julie; Hoel, Hedda; Risa, Ole J.; Romstøl, Hanna O.; Røksund, Ola; Frisk, Bente; Thorsen, Einar; Halvorsen, Thomas; Clemm, Hege H. (Frontiers in Physiology, 2017)
Purpose: Children and adolescents born extremely preterm (EP) have lower dynamic lung volumes and gas transfer capacity than subjects born at term. Most studies also report lower aerobic capacity. Aiming to unravel predictors of poor exercise capacity in EP-born subjects, we have compared their ventilatory efficiency and breathing pattern with that of term-born individuals. Methods: Two area-based cohorts of subjects born with gestational age ≤ 28weeks or birth weight ≤1000g in 1982-85 (n=46) and 1991-92 (n=35) were compared with individually matched control subjects born at term. Mean ages were 18 and 10 years, respectively. The participants performed an incremental treadmill exercise test to peak oxygen uptake with data averaged over 20 second’s intervals. For each subject, the relationship between exhaled minute ventilation (V̇E) and carbon dioxide output (V̇CO2) was described by a linear model, and the relationship between tidal volume (VT) and V̇E by a quadratic model. Multivariate regression analyses were done with curve parameters as dependent variables, and the categories EP vs. term-born, sex, age, height, weight and forced expiratory volume in 1 second (FEV1) as independent variables. Results: In adjusted analyses, the slope of the V̇E-V̇CO2 relationship was significantly steeper in the EP than the term-born group, whereas no group difference was observed for the breathing pattern, which was related to FEV1 only. Conclusion: The EP-born participants breathed with higher V̇E for any given CO2 output, indicating lower ventilatory efficiency, possibly contributing to lower aerobic capacity. The breathing patterns did not differ between the EP and term-born groups when adjusted for FEV1.